PEMANFAATAN TELEGRAM UNTUK PENDETEKSI KEBOCORAN GAS BERBASIS NODEMCU - Tri Sulistyorini; Nelly Sofi; Erma Sova (Asosiasi Dosen Muda Indonesia, 2024)
A significant increase in consumption of natural resources in the household sector is the use of LPG (Liquefied Petroleum Gas) gas, this can increase the risk of fire due to leaks from gas cylinders. These gas leaks are often unknown to users because not all LPG cylinder manufacturers provide a security system for the LPG cylinders they sell, so not all homes have gas leak sensors on LPG cylinders, therefore a tool is needed to detect LPG gas leaks. In view of these problems, in this research a device was created that can detect gas in a room with an MQ-2 sensor and apply a notification system using Telegram as an SMS notification sender and a buzzer as an alarm. The design of this detection tool as a whole is controlled by the NodeMCU ESP8226. During system testing, when a gas leak is detected at a distance of 1cm – 100cm with the MQ-2 sensor, the system will provide a notification via Telegram and activate the alarm (the buzzer will beep). The process of sending this message takes around 4-6 seconds. The tool was also tested on two different cellphones and obtained the expected results and good performance.